(untitled) - Brandt, Steven C. (Homewood, 1986)
This book is written to be used. It reflects a growing awareness that traditional garage entrepreneurs and venture capitalists and high-technology whiz kids in emerging companies cannot alone produce a healthy economy and a gratifying worklife.
Keywords: Industrial management,Quản trị công nghiệp